(untitled) - Perkins, Donald H. (Cambridge, UK, 2000)
This 4th edition includes all the recent developments in elementary particle physics, as well as its connections with cosmology and astrophysics. As in previous editions, the balance between experiment and theory is continually emphasised. The stress is on the phenomenological approach and basic theoretical concepts rather than rigorous mathematical detail. Short descriptions are given of some of the key experiments in the field, and how they have influenced our thinking
Vật lý năng lượng cao
Keywords: Particles (Nuclear physics),Hạt (vật lý nguyên tử)